4x-(3(2x-1))=7x-42

Simple and best practice solution for 4x-(3(2x-1))=7x-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(3(2x-1))=7x-42 equation:



4x-(3(2x-1))=7x-42
We move all terms to the left:
4x-(3(2x-1))-(7x-42)=0
We get rid of parentheses
4x-(3(2x-1))-7x+42=0
We calculate terms in parentheses: -(3(2x-1)), so:
3(2x-1)
We multiply parentheses
6x-3
Back to the equation:
-(6x-3)
We add all the numbers together, and all the variables
-3x-(6x-3)+42=0
We get rid of parentheses
-3x-6x+3+42=0
We add all the numbers together, and all the variables
-9x+45=0
We move all terms containing x to the left, all other terms to the right
-9x=-45
x=-45/-9
x=+5

See similar equations:

| 103-u=254 | | 2w−w=3 | | -v+216=151 | | 4=-z/5=8 | | 16n+4n=20 | | -2x+6=-4−2x+14 | | n-5=(3n+1)/2 | | 3x−12=3 | | -19=2/3x-9 | | 0.3=(2x+10) | | −9=18s | | 7e+5=6e-4 | | 7.2•10^y=3.9 | | 3m/5=-7 | | 5m+20=180 | | 3c-4=25 | | x+8=3x-7 | | -3=-9+2n | | 2p=4p-8 | | 4-5p=4p | | -6x=6x-12 | | h-8=3h+3= | | c(6-2)(c=4) | | (x-3)^2-(49)=0 | | -10=2x+6=4 | | 13-4n=83 | | 3m+(-8)=-25 | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999x+349857093457342753240785709834270998572983475342752347059843787258634756374256093284620376518506347568273456425847358093479205720875982708347572369804375893475 | | 3(x-4)+3=2x-9+x | | 6x+9=0968349684-8 | | 4389265769432792665765736583726532768957634875678324952346598723465783462789x+54983458234659834260786598342658734265834279569823475068734597623984765234329875467562349658275643875687342567234692756873=85978094570734598237508243705438534872534563295 | | 4x+14=21 |

Equations solver categories